Political transition and determinants of liquidity creation in middle East and North Africa countries - Abraheem, Nagea (2020)
Political transition is one of the political risks that can lead towards discontinuity in economic activities. Unsurprisingly, political transition (Arab Spring) in the MENA region has affected its economy. The banking sector, being a crucial element in the financial system, is not spared. Liquidity creation is one of the main functions of banks that can be affected by various factors. This study aims to examine the impact of political risk, bank-specific factors, banking industry factors and macroeconomic factors on liquidity creation; vis-a-vis political transition (Arab Spring). Bank type (i.e. Islamic or conventional), availability of deposit insurance system and bank size were included as control variables in this study. The study sample included 55 Islamic and conventional banks from Arab Saudi, Bahrain, Egypt, Jordan, Kuwait, Lebanon and Tunisia for the period between 2006 and 2015. In the period of pre-political transition, the findings revealed a positive relationship between liquidity creation and political risk, indicating that political instability diminishes liquidity creation. However, bank capital, stability of bank, competition, stability of banking industry, unemployment and economic growth, negatively influenced liquidity creation. For the period of post-political transition, similar results were estimated regarding liquidity creation relationship with political risk, stability of bank, stability of banking industry and unemployment. Nevertheless, the findings in the post-Arab Spring period were in contrast with the results of pre-political transition regarding the liquidity creation relationship with competition and economic growth. Moreover, in the period postpolitical transition, bank capital has no effect on liquidity creation, while nonperforming loans positively influenced liquidity creation. It was notable that there was no difference between the results for Islamic and conventional banks. Also, the availability of deposit insurance system reduced liquidity creation in both periods. This study provides a new perspective on the relationship between liquidity creation and political risk. It extends the empirical and theoretical aspects of research and offers more comprehensive and empirical views on how liquidity creation is influenced by banks’ specific factors, banking industry factors and macroeconomic factors in pre and post- political transitions. The findings can provide early warning of risks that banks are likely to face in liquidity creation. Regulations should focus on banking supervision quality by adopting policy measures that increase competition and maintain banks’ stability.